Ethical issues associated with assistive technologies for persons living with dementia and their caregivers: An overview of reviews - Scerri, A.; Juul, F. S.; Silva, R.; Serrat, R.; Grech, A.; Fedosejeva, G. J.; Celdrán, M.; Trypka, E.; Xuereb, C. B.; Korkmaz-Yaylagul, N.; Evripidou, M.; Machado Alexandre, I.; et al. (Dementia: International Journal of Social Research and Practice, 2026)
Assistive technologies hold significant potential to enhance the quality of life for persons with dementia and their caregivers by addressing key concerns related to safety, independence, and social inclusion. Although ethical issues surrounding the design and use of assistive technologies have been explored in various studies, no comprehensive overview of reviews has been conducted to synthesize the existing evidence on these issues. This study aims to categorize the ethical issues associated with assistive technologies for persons with dementia and their caregivers using established ethical principles, while also examining factors shaping the ethical debate on their design and implementation. The study was conducted across nine databases and included reviews published in the past 20 years that substantially addressed ethical considerations. Data synthesis followed the framework synthesis approach developed by Carroll et al. (2011). Out of 509 identified records, 15 reviews focusing significantly on ethical issues were included in the analysis. Findings revealed key ethical issues, including maintaining autonomy, respecting privacy, and addressing equity and accessibility. While assistive technologies demonstrate potential in enhancing safety and independence, concerns about surveillance, depersonalization, and stigmatization persist. The ethical debate is shaped by contextual, philosophical, temporal, and geographical factors, including varying stakeholder priorities, the fluctuating nature of dementia symptoms, diverse approaches to dementia care and ethics, cultural differences, and the implications of future technological advancements. This review underscores the complexity of ethical issues related to assistive technologies for dementia care and how these identified factors inform the ethical design and their use for persons with dementia and their caregivers.